A pilot study to assess the efficacy of VCare predict in early detection of pressure ulcer - Bellarmin, Edison; Ramasamy, M. S. (International Journal of Clinical Trials, 2022)
Background: The aim of the study to evaluate the efficiency of ‘VCare’ predict for early diagnosis of pressure ulcers/bedsores/pressure injury are a type of injury that breaks down the skin and underlying tissue leading to reddening of the skin to severe, deep craters with exposed muscle or bone necrosis. A pilot study was carried out to assess and compare efficacy of VCare predict and standard of care (SOC) in prediction of pressure ulcer among the high-risk patients being hospitalized. Methods: The 30 female or male subjects aged ˃60 years were selected with inform consent and enrolled in the study. The efficiency of VCare predict was evaluated by comparison of arm A (VCare predict) and arm B SOC. The sensor patch is placed under sacrum for 30 seconds. It captures key parameters and transfer to the mobile app thru blue-tooth. Mobile app receives measured data, and it shows the risk level of the patient (Red, Yellow and Green) to recommend the frequency of flip to predict the early diagnosis of severity of pressure ulcer. Results: The study results exemplified that efficiency of VCare predict which is more efficiently (with 31.4% lesser flips in Arm A) predict pressure injury leading to further complications. Conclusions: This study was concluded that VCare predict can be a highly effective risk assessment and mitigation tool in pressure ulcer management. With VCare predict, there was no adverse event found or experienced, hence it is a safer tool to use.